Propaganda image of the Operation Cedar Falls in January 1967 during the Vietnam War - Masny, Patryk (The phenomena of propaganda and manipulation in the press, radio, television, and internet. Volume II, 2023)
The article aims to analyse the operation Cedar Falls (8 to 26 January 1967) propaganda image based on American, North Vietnamese and Polish materials. Cedar Falls was the largest offensive since of the begging of the Vietnam War, engaging nearly 30 000 US and South Vietnamese soldiers. In the after action reports, the Operation was considered a significant success. Therefore, it is not surprising that due to its scale and course, it has become an object of propaganda. In the article, I discuss, and analyse its image in the materials mentioned above and show similarities and differences between them. I examine whether the propaganda representation of this Offensive in polish “Trybuna Ludu” is different from the one shown in the North Vietnamese materials taking into account that both of these countries belonged to the same Cold War bloc. Analyse to what extent the propaganda image of this Operation, at respective sides, is consistent with the actual course of events and why and how certain elements have been changed. The specific motives of each material are worth of emphasizing. In the "Trybuna Ludu" to merge Operation Cedar Falls and the unsuccessful operation Deckhouse V carried out almost at the same time in the Mekong Delta, trying to extend the failure of the latter to Cedar Falls. Trybuna” has written about the displacement of refugees from the Iron Triangle to concentration camps, thus connecting Americans in Vietnam with Germans during WW II. American materials attempts to emphasize humanitarianism, allegedly unique on a historical scale, towards the inhabitants of the Iron Triangle. Vietnamese communist propaganda significantly overestimated of the losses of Americans in the Operation and accuses them of using chemical weapons in the form of toxic gases.